Structure, thermophysical, antimicrobial, and genotoxic properties of silver-containing nanocomposites film, obtained by sputtering deposition - V. L. Demchenko; Ye. P. Mamunya; M. V. Iurzhenko; S. M. Kobylinskyi; N. P. Rybalchenko; T. T. Hnatiuk; T. V. Rybalchenko; A. I. Marynin; D. V. Shtepa; I. O. Sytnyk; O. M. Demchenko; S. R. Rushkovsky (Хімія, фізика та технологія поверхні, 2025)
To create film materials with antimicrobial properties, silver nanoparticles are widely used, which are introduced, in particular, into polymer matrices. In this work, a mixture of polylactide-polycaprolactone polymers, taken in a mass ratio of 80–20, was used as a polymer base. These studies will further contribute to the development of new safe materials, particularly in creating packaging materials for food products, which is undoubtedly an urgent problem today.